Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Mahasiswa Pada Sekolah Tinggi Teknologi Payakumbuh - Rionardi Rionardi; Almasdi Almasdi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2019)
The purpose of this study was to analyze the effect of service dimension variables on student satisfaction with educational services. The study was conducted using a quantitative approach. The sample of this study were students Sekolah Tinggi Teknologi Payakumbuh a total sample of 123 students. Data analysis for hypothesis testing uses binary logistic regression. The results showed the First Hypothesis (H1): Simultaneous testing all dimensions of service quality that significantly influence student satisfaction are tangibles (X1), reability (X2), responsiveness (X3), and assurance (X4), while empathy variables (X5) ) has no significant effect with the level of student satisfaction contribution to services at STT Payakumbuh at 88.1% and 11.9% influenced by other variables. Second Hypothesis (H2): Testing that can be seen partially so that it can be seen that the most dominant dimension affecting service satisfaction at the Sekolah Tinggi Teknologi Payakumbuh (STTP) is the responsiveness variable (responsiveness) that can provide increased student satisfaction with academic services by 151,109 times more high compared with students who are not satisfied and when compared with other variables also have the most dominant influence with the logistic equation model of the effect of service quality variables on student satisfaction is logit (Y) = -3,985 + 2,999TG + 2,177REA + 5,260RESPN + 2,803ASSRC. It is expected that STT Payakumbuh needs to improve the quality of service in increasing the level of student satisfaction with educational services.